Hunt, Ed., The French Revolution And Human Rights - A Brief Documentary History, Blanning, The French Revolutionary Wars, 1787-1802 - Morris, Marilyn (Teaching History: A Journal of Methods, 1997)
In the absence of a new, all-encompassing interpretation of the French Revolution of 1789 to replace the seductively simple Marxist triumph of the bourgeoisie, its historiography has become kaleidoscopic. Hence, the Revolution provides the perfect training ground for buildings students' analytical skills. When confronted with the multiplicity of perspectives on the Revolution, they quickly realize how present preoccupations bear upon our view of the past, as well as how our view of the past influences present attitudes and assumptions.